Vodohospodářské řešení malé vodní nádrže Tršice - Chyba, Martin (Vysoké učení technické v Brně. Fakulta stavební)
Úkolem bakalářské práce je vhodné vodohospodářské řešení zásobní funkce a ochranné funkce malé vodní nádrže Tršice. Součástí práce je provedení výpočtu zabezpečenosti nádrže při různých hodnotách součinitelů zabezpečenosti a různých úrovní přelivné hrany bezpečnostního přelivu. Dále bude provedena transformace povodňových vln.

The aim of the Brachelor thesis is appropriate design water managment solution of storage tank function and protective function of small water resevoir Tršice. Part of the thesis is performing the calculation of safety reservoir during different values of security coefficients and different levels of overflow edge of safety edge. Will be perfomed transformation of flood waves.
Water management solution of Tršice small water reservoir
Keywords: nádrž; vodohospodářské řešení; zásobní objem; povodňová vlna; transformace povodňové vlny; Tršice; reservoir; water management solution; storage tank; flood wave; transformation of flood wave; Tršice